‘You don’t need schooling—just take the pills and don’t stop.’: Pathways between formal education and chronic HIV care in Malawi - Stephanie Chamberlin; Misheck Mphande; Pericles Kalande; Khumbo Phiri; Kathryn Dovel (SSM: Qualitative Research in Health)
Research on chronic care management from other settings indicates that people’s formal education (e.g., primary, secondary, and tertiary schooling) may confer important cognitive skills and material resources to help them manage their chronic HIV care and treatment. However, recent population-level findings from southern and eastern Africa suggest no statistical relationship between education and chronic HIV care. To gain additional insight into these puzzling findings, we draw on in-depth interviews with HIV care clients in Malawi to understand how people acquire education-related resources and how they use such resources to support their HIV care. These interviews suggest that education-related cognitive and material resources are central to HIV care management, but such resources are not necessarily gained through formal schooling. Importantly, HIV clients use a variety of strategies to overcome their limited skills and resources, often relying on the literacy and material resources of their family and community to facilitate their HIV care. Taken together, these findings provide new insight into the mechanisms that link or attenuate education-health relationships in different contexts globally. Further, this work informs the development of more equitable chronic care interventions for meeting the needs of people across different education levels.